DAYA DUKUNG LAHAN PERMUKIMAN KECAMATAN GUNUNGPATI - Rahmat Hirmawan; Bitta Pigawati (Teknik PWK (Perencanaan Wilayah Kota), 2022)
The existence of the Semarang State University College in Gunungpati District can attract residents to come and have activities in the educational area. This condition causes an increase in population and expansion of residential areas in Gunungpati District. It is feared that the phenomenon of the expansion of uncontrolled residential areas could lead to environmental degradation. This study aims to assess the carrying capacity of residential land in Gunungpati District based on an analysis of land suitability and land capability referring to the Minister of Public Works Regulation No. 20 of 2007. Using a spatial approach method with weighting and scoring analysis techniques. The results showed that the carrying capacity of residential land in Gunungpati District varied from low to high carrying capacity. Most of the Gunungpati area has a low land carrying capacity, but it can still be developed for settlements if improvements are made to infrastructure and water availability, while the Sekaran Village area is the best location for residential areas because it has high land carrying capacity based on various aspects of consideration.